(untitled) - Genzel, Rhona B. (Boston, Massachusetts, USA., 1994)
Students learn to speak and act comfortably in a new culture by sharing cultural thoughts, notions, and experiences, and comparing these with the behaviors, customs, and everyday situations common to life in North America.
Giao tiếp liên văn hóa,Văn hóa các nước nói Tiếng Anh
Keywords: English language,English language,Giáo trình tiếng Anh,Đàm thoại và thành ngữ tiếng Anh; Textbooks for foreign speakers.,Conversation and phrase books